Agricultural financing initiatives in developing countries: Can microfinance fill The gap? The case of Iringa Rural district, Tanzania - Munuo, Catherine (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the Master of Economics in Project Planning and Management (MSC.PPM) of Mzumbe University